A feasibility study of "Bunchies" as a licensed brand of Closet Design, Inc. - Elizaga, Claudine Veronica S.D
This study will determine the feasibility of CDI becoming a licensee company of "Bunchies, Inc." by providing the following: an organizational chart of the Bunchies division in CDI, a five-year sales projection plan, three buying plans for the different divisions, a costing formula and sample costing computations, and lastly, a sample portfolio of the Bunchies collections. The result of this study provide a clear and concise concept on the proper procedure that CDI should take in gaining the Bunchies license and have better control on its product development.